Morphological Variations of the Cusp of Carabelli in Permanent Maxillary First Molars and Their Correlation with Caries Risk in the Peshawar Population: Cusp of Carabelli in Permanent Maxillary First Molars and Their Correlation with Caries Risk - Dil, Farhan; Syed Umer Farooq; Sattar, Asma; Imran, Naheed; Khattak, Ammar; Khan, Muhammad Adnan (Pakistan Journal of Health Sciences, 2026)
The Cusp of Carabelli is a common non-metric morphological trait of permanent maxillary first molars. Although its anthropological significance is well recognized, its clinical relevance in relation to dental caries remains controversial, with limited regional data from Khyber Pakhtunkhwa. Objectives: To determine the prevalence and morphological patterns of the Cusp of Carabelli and evaluate their association with caries risk in a young population of Peshawar. Methods: A descriptive cross-sectional study was conducted at the Dental Outpatient Department of Khyber College of Dentistry, Peshawar. A total of 103 participants aged ≥12 years were examined using non-probability consecutive sampling. The Cusp of Carabelli was assessed on teeth 16 and 26 using the ASUDAS/Dahlberg classification (Types 0–6). Caries experience was recorded using the DMFT index. Oral hygiene behaviors were obtained through a structured questionnaire. Data were analyzed using descriptive statistics, chi-square, independent t-test, and Pearson correlation. Results: The Cusp of Carabelli was present in 62.1% of participants, with a mean severity score of 1.47 ± 1.41. The mean DMFT score was 4.48 ± 2.42, and 53.4% were classified as high caries risk. No significant associations were observed between Carabelli morphology, side expression, or severity score and caries experience (p>0.05). Oral hygiene behaviors also showed no significant association with caries risk. Conclusions: The Cusp of Carabelli is common in the studied population; however, its presence and morphology do not significantly influence caries risk and should be regarded primarily as a normal anatomical variation.